The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1073/pnas.1412849111
|View full text |Cite
|
Sign up to set email alerts
|

Order and disorder control the functional rearrangement of influenza hemagglutinin

Abstract: Influenza hemagglutinin (HA), a homotrimeric glycoprotein crucial for membrane fusion, undergoes a large-scale structural rearrangement during viral invasion. X-ray crystallography has shown that the pre-and postfusion configurations of HA 2 , the membranefusion subunit of HA, have disparate secondary, tertiary, and quaternary structures, where some regions are displaced by more than 100 Å. To explore structural dynamics during the conformational transition, we studied simulations of a minimally frustrated mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 40 publications
4
78
0
Order By: Relevance
“…The SBS 10 have indicated that an order-disorder transition of Loop3-4 (Fig. 1A,B) is integral to initiating the HA 2 rearrangement.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…The SBS 10 have indicated that an order-disorder transition of Loop3-4 (Fig. 1A,B) is integral to initiating the HA 2 rearrangement.…”
Section: Introductionmentioning
confidence: 98%
“…7 The post-fusion structure of HA 2 was obtained under low pH conditions and trimmed to remove the fusion peptides (FPs). 8,9 Comparison with the pre-fusion structure reveals dramatic changes in secondary, tertiary, and quaternary structure, 8,10 which opens the possibility of long-lived intermediate ensembles. Therefore, any search for structure-based therapeutics is incomplete without an understanding of the paths HA 2 follows during its conformational rearrangement.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations